Afghanistan’s Forced Displacement Legal and Policy Framework Assessment - World Bank Group (World Bank, Washington, DC, 2018)
This Assessment is conducted as part of a larger platform established in 2016 through a joint World Bank and UNHCR initiative to support Afghanistan’s forcibly displaced population. The platform aims to inform and support the dialogue between stakeholders in Afghanistan in order to: (i) seek ways to ensure a meaningful inclusion of durable solutions for the forcibly displaced and returnees in the Afghanistan National Peace and Development Strategy (ANPDF) and development intervention; (ii) identify early recovery and long-term needs of the forcibly displaced persons; and (iii) identify policy level and developmental opportunities that can contribute to the well-being and self-reliance of Internally Displaced Persons (IDPs), returnees, refugees and their host communities. One of the main activities under this joint initiative is Policy and Implementation Analysis, which includes an assessment of Afghanistan’s legal and policy framework on forced displacement.3 Afghanistan’s Forced Displacement Legal and Policy Framework Assessment was prepared during the period of January to May 2017 as part of efforts towards completion of this main activity. This assessment recommends that Afghanistan establish an effective and comprehensive legal and policy framework that provides protection to all categories of forcibly displaced persons, including asylum seekers, refugees, and stateless persons. Furthermore, this assessment recommends reforms in the existing legal and policy instruments that address the specific needs of forcibly displaced persons and promote their access to basic human rights and public services. These include reforms in the following areas: establishment and maintenance of effective registration and data collection system on forced displacement; facilitated access to documentation and simplified procedure for replacement of lost and/or damaged documents; promotion of the forcibly displaced persons’ access to land, shelter and housing as well of their land tenure security; harmonization of legal and policy frameworks to ensure compliance with the IDP Policy and the National Policy Framework; and provision of sufficient resources to institutions put in place or responsible for implementing the forced displacement legal and policy framework.